Chiral Self‐Assembly of Twisted Prisms, Cuboids, and Polyhedral Capped Cages with Tartrate Ligands - Mu, Qiu‐Shui; Wang, Xin‐Yu; Gao, Xiang; Jin, Guo‐Xin (Small (Weinheim an der Bergstrasse, Germany), 2024)
Homochiral triangular prisms, cuboid cages, and capped polyhedral cages are successfully synthesized via coordination‐driven self‐assembly. Typical tartrate ligands demonstrated notable torsional flexibility and variable coordination numbers, allowing for diverse coordination patterns, including saturated chelation and terminal mono‐coordination with half‐sandwich rhodium and iridium fragments. The ligand lengths, molar ratios, and metal vertices are meticulously designed and fine‐tuned to yield chiral cages with entirely distinct architectures. Tartrate ligand exhibits abundant hydrogen bonding interactions and chiral induction capabilities, these supramolecular assemblies are characterized by single‐crystal X‐ray diffraction, nuclear magnetic resonance, and circular dichroism spectroscopy. An efficient method is developed for constructing chiral structurally versatile cage‐like entities, facilitating self‐assembly in complicated multi‐component systems. Chiral twisted prisms, cuboids, and capped cages are constructed through the full utilization of flexible tartrate ligands. The self‐assembly of different components in varying ratios, coupled with the use of ligands that can accommodate a range of coordination numbers, has enabled the emergence of a rich array of coordination patterns.